2010
DOI: 10.1007/s11605-010-1195-x
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Randomized Controlled Trials that Compared Laparoscopy-Assisted and Open Distal Gastrectomy for Early Gastric Cancer

Abstract: LADG is advantageous over ODG because it results in lesser blood loss, is less painful, and is associated with a low risk of complications. Additional RCTs that compare LADG and ODG and investigate the long-term oncological outcomes of LADG are required to determine the advantages of LADG over ODG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
67
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(75 citation statements)
references
References 23 publications
3
67
2
1
Order By: Relevance
“…Many studies have shown the advantages of LADG over open distal subtotal gastrectomy (ODSG), such as cosmetic benefits, less pain, faster recovery, and shorter hospital stay [2][3][4][5][6][7]. The early postoperative quality of life (QoL) following LADG has been shown to be superior to that following ODSG [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown the advantages of LADG over open distal subtotal gastrectomy (ODSG), such as cosmetic benefits, less pain, faster recovery, and shorter hospital stay [2][3][4][5][6][7]. The early postoperative quality of life (QoL) following LADG has been shown to be superior to that following ODSG [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Others reported no difference between the laparoscopic and open approaches. 15,16,[26][27][28][29][30][31]33 In a meta-analysis of RCTs comparing laparoscopic and open approaches for early gastric cancer, Ohtani and colleagues 9 concluded that there was a lesser number of LNs with laparoscopy. Debate is still ongoing about the extent of the lymphadenectomy and the number of LNs needed in the specimen.…”
Section: Discussionmentioning
confidence: 99%
“…The extensive Asian experience, where gastric cancer is diagnosed at an early stage, has confirmed the adequacy of laparoscopic resection with regards to postoperative outcomes, technical feasibility of appropriate lymphadenectomy and oncologic outcomes. [7][8][9][10][11][12] In Western countries, where gastric cancer is less prevalent and diagnosed at an advanced stage in 75% of patients, 13 laparoscopic gastrectomy has not yet been ac cepted as a curative treatment. Therefore, conclusions regarding the treatment in large Asian trials cannot be generalized to Western patients.…”
mentioning
confidence: 99%
“…Many potential benefits of the procedure, such as less bleeding, early recovery, and good cosmetic results, compared with conventional open gastrectomy (OG) have been reported, and the safety of the procedure was confirmed by randomized trials conducted in Asia (2)(3)(4)(5)(6)(7)(8). Equivalent long-term survival outcomes in patients with early gastric cancer were also reported in a randomized control trial (9).…”
Section: Introductionmentioning
confidence: 95%